2022
DOI: 10.3390/app12189054
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Post-Activation Performance Enhancement on Jump Performance in Elite Volleyball Players

Abstract: Post-activation performance enhancement (PAPE) is a widely described phenomenon, but the majority of studies tend to evaluate the response of various parameters of a conditioning activity (CA) on the same explosive exercise. The aim of this study was to evaluate the PAPE response of the same CA—trap bar deadlift with an accommodating resistance—on jump height in two different jumping tests: squat jump (SJ) and countermovement jump (CMJ). Study participants included twelve elite volleyball players (age 23 ± 2 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…Moreover, certain studies proved that the accommodating resistance was more effective in comparison to free weight resistance [ 21 , 23 , 25 ] in inducing PAPE. Even though a trap bar deadlift was suggested as being an effective training alternative to a squat, [29] there is little evidence of a trap bar deadlift inducing PAPE [ 30 – 34 ]. The results of the studies using only traditional resistance are not consistent - two of them showed no PAPE effect [ 30 , 31 ], whereas one of them enhanced subsequent explosive performance.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Moreover, certain studies proved that the accommodating resistance was more effective in comparison to free weight resistance [ 21 , 23 , 25 ] in inducing PAPE. Even though a trap bar deadlift was suggested as being an effective training alternative to a squat, [29] there is little evidence of a trap bar deadlift inducing PAPE [ 30 – 34 ]. The results of the studies using only traditional resistance are not consistent - two of them showed no PAPE effect [ 30 , 31 ], whereas one of them enhanced subsequent explosive performance.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a trap bar deadlift was more effective compared to a back squat [ 32 ]. Additionally, there are two studies [ 33 , 34 ] where the accommodating resistance was used while performing a trap bar deadlift. Both of them [ 33 , 34 ] involve a vertical jump component as an explosive exercise.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations